ANALISIS VARIANS BIAYA PRODUKSI SPEED BOAT FIBER GLASS PADA PT BUAN NUSA RESPATI SAMARINDA TAHUN 2014-2018 (Studi Kasus: pada Perusahaan Manufaktur yang Terdaftar di Samarinda (2014-2018) - Sucipto Sucipto; Farindika Metandi; Novia Nurindah (Politeknik Negeri Samarinda, 2019)
The objectives of this research is to determine the favorable variance for the cost of production of small marine speed boat fiber glass 7.20 M x 2.40 M x 1.25 M PT Buran Nusa Respati Samarinda in 2014 s / d in 2018 and what causes favorable variance. The analytical method used is the analysis of variance. The result of the study shown that variance occurs in the production cost of small marine speed boat fiber glass 7.20 M x 2.40 M x 1.25 M in 2014, 2015, 2016, 2017, and 2018 are the difference in production costs is the increase and decrease in the purchase price of raw materials and the amount of raw material purchases, the increase and decrease in the number and hourly rate processing employee and increase and decrease of factory overhead costs. Keywords: Analysis of Variance, Cost of production, and Favorable Variance.